Early repolarization is associated with significant coronary artery stenosis in asymptomatic adults. (February 2016) - Suh, Beomseok; Park, Sehhoon; Shin, Dong Wook; Ahn, Hongkeun; Cho, Seongcheol; Lee, Seung-Pyo; Park, Eun-Ah; Lee, Hyejin; Park, Jin Ho; Cho, BeLong
Abstract: The aim of our study was to investigate the relationship between early repolarization (ERP) and coronary heart disease (CHD) by evaluating its association with coronary artery stenosis and plaques. Consecutive asymptomatic adults aged 30 or more without CHD were investigated (n = 3100). Adjusting for major cardiovascular risk factors, ERP was significantly associated with significant coronary stenosis with incremental predictive value (aOR 1.71, 95% CI 1.13–2.60; ROC AUC 0.763 vs. 0.723, P < 0.001; NRI 4.86%, P = 0.042; IDI 0.0030, P = 0.040), specifically in intermediate risk group (aOR 2.33, 95% CI 1.29–4.20; ROC AUC 0.753 vs. 0.708, P = 0.001). ERP was shown to be especially associated with significant coronary stenosis with non-calcified plaque (aOR 2.26, 95% CI 1.28–3.98). Our study is the first to directly show the association of ERP with CHD. Future studies are needed to replicate our results and investigate whether it would be beneficial to include ERP in risk algorithms for CHD screening.